Analisis Proses Penetrasi Sosial dalam Membangun Hubungan Interpersonal melalui Fitur Telepath Aplikasi Omi : Studi Kasus Masyarakat di Kelurahan Margahayu, Bekasi Timur - Fitri Nuraini; Mareta Puri Rahastine; Anggie Ayu Astria Latuperrisa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to understand how users of the OMI app build interpersonal closeness and engage in self-disclosure through the Telepath feature. The OMI app is a digital dating platform used within the social circles of the Margahayu neighborhood in East Bekasi. Through the Telepath feature, users can chat via anonymous voice calls within a specific time limit, so that their physical appearance is not visible when a new conversation begins The theory used to support this research is the Social Penetration Theory by Irwin Altman and Dalmas Taylor. This study was designed using a descriptive qualitative method with a case study approach to capture the users’ perspectives. All data were collected through observation, in-depth interviews with five active user informants, and supplemented with documentation. The research findings indicate that the communication among the five informants progressed through the stages of a relationship, starting from anonymous introductions, moving to in-depth conversations, and culminating in the decision to share real photos each other. However, the level of intimacy achieved was not always the same; the majority of informants were able to advance their closeness to a more personal level such as exchanging personal contact information or meeting in person, while others had to stop due to various obstacles.